The utilization of bio-booklet of plants diversities based on local potency to enhance student’s conservation attitudes and skills for classification - S Lestari; S Sriyati; Amprasto Amprasto (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Community-based natural resources in Indonesia are highly diverse and notably important as potential learning resources. One of those local potencies lies in Taman Hutan Kota Langsa. The classroom activities were conducted through the use of bio-booklet containing near extinct plants and native plants of Aceh that existed in Taman Hutan Kota Langsa. With regard to this issue, the current study was carried out to enhance classification skills and conservation attitudes of young learners during field trip to Taman Hutan kota Langsa. The samples of this study were first grade students of SMA Negeri 5 Langsa. Data of conservation attitudes were obtained from questionnaire, whereas data of classification skills were collected using pretest-posttest and student worksheet. In addition, the data were analyzed using mean-difference test and normalized gain score. Preliminary study disclosed that Taman Hutan Kota Langsa is importantly feasible to be learning resource because of its 80 plants species which consist of 5 vulnerable extinct plants and 5 native plants of Aceh. According to the interview with biology teacher from SMA Negeri 5 Langsa, conventional lessons with text-books and indoor learnings were still not effective to enhance classification skills and conservation attitudes of students.